Morphological Features of the Surah Al-Insyirah and its Translation into English by Students of English Education Department at Universitas Islam Madura - Nur Imamah Yuliatin; Dinar Vincy Yunitaka Bahrudin; Fitrah Yuliawati (Universitas Islam Negeri Palopo, 2026)
This research investigates the morphological features of the surah Al-Insyirah and examines how the fourth semester students of English education department at Universitas Islam Madura translate the surah Al-Insyirah into English. Grounded in morphological theory (Adisutrisno, 2013) and translation studies Hatim (2014) this research used a qualitative method with a case study approach employs observation, interview, and documentation. The finding reveal that surah Al-Insyirah contains rich distributions of free morpheme and bound morpheme that carry grammatical and semantic functions which significantly influence meaning reconstruction in English. Students translation show varied handling of inflectional and derivational morpheme, level shifts, and translation methods affecting accuracy and contextual appropriateness. The research highlights is the importance of morphological awareness in Holy Qur’an translation task and contribute to applied linguistic in English language education.